Dyadic Dynamics: The Impact of Emotional Responses to Facial Expressions on the Perception of Power - Hareli, Shlomo; Halhal, Mano; Hess, Ursula (Frontiers in Psychology, 2018)
Emotion expressions play a central role in social communication, which, by definition is a dynamic process. Social communication involves the exchange of signals with temporal dynamic properties between two or more individuals. Nonetheless, emotion perception research has strongly focused on the study of single, static, unidirectional images. The goal of this research is to illustrate the dynamic nature of emotion communication by showing how the back and forth of a dyadic emotional interaction affects its perception by uninvolved observers. To that aim, we conducted three studies that investigated how observer’s inferences of social power are influenced by an exchange of emotions between members of a dyad. In Study 1, participants saw one person showing either anger or sadness to which the second member of the dyad reacted by showing either anger, fear or neutrality. In Study 1, only still photos were shown in sequence. In Studies 2 and 3, more dynamic stimuli and other emotions were included. Even though an angry expresser was always perceived as more powerful than a sad expresser, the emotional reactions of the interaction partner modulated perceived power. Across all three studies and different levels of dynamic stimuli, fear reactions always increased perceived power. Happiness, contempt and neutrality affected perceived power more selectively. This effect was mediated by the extent to which participants felt that the reaction of the second interaction partner suggested that the second interaction partner agreed with regard to the power differential between the two. Taken together, these experiments show that the social signal value of emotion expressions changes meaningfully as a function of the emotional response of the expressions’ target. Thus, the social signal value of emotions does not stand alone but has to be understood in the fuller context of the interaction.